Do banks price environmental transition risks? Evidence from a quasi-natural experiment in China - Huang, Bihong; Punzi, Maria Teresa; Wu, Yu (Journal of Corporate Finance, 2021)
This paper assesses the risk arising from transition toward a low-emission economy and examines its transmission channels within the financial system. The environmental dynamic stochastic general equilibrium (E -DSGE) model shows that tightening environmental regulation impairs firms' balance sheets in the short term, as it enforces firms to internalize the pollution costs, which consequentially escalates the risks facing the financial system. For the empirical analysis, we employ the Clean Air Action that the Chinese government launched in 2013 as a quasi-natural experiment. The analysis on a unique dataset containing more than one million loans indicates that the default rates of high-polluting firms rose by around 80% along their environmental policy exposure. Further analysis shows those joint equity commercial banks with lower degree of government intervention and better corporate governance structure were able to appropriately manage their exposure to transition risks, while the state-owned banks failed to factor in such risks when extending credit to the borrowers targeted by the environmental regulation.